Modified poly-L-lysine for use as a clearing agent in pretargeted radioimmunotherapy - Chiara Timperanza; Anna Gustafsson-Lutz; Tom Bäck; Damian J. Green; Sture Lindegren; Emma Aneheim (SpringerOpen, 2024)
Abstract Background Pretargeted radioimmunotherapy of cancer has the potential to increase tumor specific uptake of activity when compared with conventional radioimmunotherapy. This is especially true in radioimmunotherapy with nuclides that exhibit a relatively short half-life. When administering antibody-based pretargeting molecules systemically, the antibodies often show a relatively slow clearance from the blood. Therefore, the use of a clearing agent is advantageous to remove unbound pretargeting molecules from the circulation, facilitating a reduction in the nonspecific radiation exposure to normal tissue while maximizing the dose delivered to the tumors. Results In the current study, two types of poly-L-lysine based clearing agents were produced for two different pretargeting systems: (strept)avidin/biotin and Tetrazine/Transcyclooctene. Poly-L-lysine was used as scaffold for production of clearing agents. The polymer is available in multiple sizes and can readily be modified with several functional groups, allowing different pretargeting strategies to be used. In vivo evaluation of the biotin-functionalized poly-L-lysine clearing agent, 110 repeating units, resulted in a decrease in blood concentration of the Iodine-125 labeled pretargeting agent of 50%, circa 23 h after injection, compared to controls. Two sizes, 68 and 143 repeating units, of the tetrazine-functionalized poly-L-lysine clearing agent were also evaluated, which at 23 h after injection decreased the blood concentration of the Iodine-125 labeled pretargeting agent to 58 and 38% respectively. Conclusion The straightforward synthesis of poly-L-lysine based clearing agents makes kit preparation possible and these agents show good potential for further evaluation, especially within the Tetrazine/Transcyclooctene pretargeting system where no liver or kidney accumulation was observed.